Four signalling domains in the hybrid histidine protein kinase RodK of Myxococcus xanthus are required for activity. - Rasmussen, A; Wegener-Feldbrügge, S; Porter, S; Armitage, J; Søgaard-Andersen, L (2006)
In prokaryotes, the principal signal transduction systems operating at the level of protein phosphorylation are the two-component systems. A number of hybrid histidine protein kinases in these systems contain several receiver domains, however, the function of these receiver domains is unknown. The RodK kinase in Myxococcus xanthus has an unconventional domain composition with a putative N-terminal sensor domain followed by a histidine kinase domain and three receiver domains. RodK is essential for the spatial coupling of the two morphogenetic events underlying fruiting body formation in M. xanthus, aggregation of cells into nascent fruiting bodies and the subsequent sporulation of these cells. RodK kinase activity is indispensable for RodK activity. By systematically substituting the conserved, phosphorylatable aspartate residues in the three receiver domains, genetic evidence is provided that each receiver domain is important for RodK function and that each receiver domain has a distinct function, which depends on phosphorylation. Biochemical analyses provided indirect evidence for phosphotransfer from the RodK kinase domain to the third receiver domain. This is the first example of a hybrid histidine protein kinase in which four signalling domains have been shown to be required for full activity.